The local terms in the pre war novel of the MCA's new literature - Ang, Lay Hoon; Tan, Ming Swee (2013)
Being a continuation of entity, the Chinese literature in Singapore and Malaysia are similar to the Chinese literature in China and yet may differ in some aspects. This paper focus on the lexical difference in terms of the usage of Chinese dialects and local languages, such as Malay language and English language, found in Singaporean and Malaysian Chinese fiction. The data were collected from literary works compiled by FangXiu in Malayan Chinese New Literature (1919-1942) Fiction Collection I & II (Book III & IV). The terms of five main local languages could be identified, namely Cantonese, Minnan, local Chinese language, Malay and English. The dialectal and local vocabularies used in fictions formed a unique characteristic of Chinese fictions in Malaysia and Singapore which is different from Chinese fictions in other parts of the world.